Audio-visual language for creation of identity of rural settlements of the city of Pedras Altas – RS - Bedin, Daiane Teresa; Rehn, Rafael Luiz; Hoppe, Barbara Chiodini i Axt; Medeiros, Liziany Muller; Chies, Jacir João; Silva, Nayra Grazielle da; Pinheiro, Rogério Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
With the spread of new communication resources and the idea of participatory culture, the objective is to show how a collaborative audiovisual production independent and has the ability to build and affirm the identity of a group, through discourse with images and sounds. Documented experience occurs in rural agrarian reform settlements in the municipality of Pedras Altas. The movement seeks to delineate their social, cultural and especially economic identity, seeking the production of an audiovisual, construction of meanings to be shared with the company.